비선형파를 고려한 비대선의 선수선형설계에 관한 연구 - 유진원(Jin-Won Yu); 이영길(Young-Gill Lee); 최시영(Si-Young Choi); 최영찬(Young-Chan Choi); 정광열(Kwang-Leol Jeong); 하윤진(Yoon-Jin Ha) (大韓造船學會 論文集, 2010)
This paper introduces a new hull form design method for the bow of a full ship, by actively applying the relation between the fore-body hull form and its wave resistance characteristics. For the hull form design, the Series 60($C_B=0.8$) hull is chosen as the parent ship, and Kracht's charts are used to determine the parameters of the bulbous bow in the early stages of hull form design. Several hull forms have been tested in order to obtain enough hull form variations with various bow shapes and design parameters in the search of the best design. In order to investigate the resistance characteristics of the designed hull forms, numerical simulations with corresponding model tests have been rigorously performed. For the numerical simulations, the Marker-density method is employed to track the nonlinear phenomena of the free surface(program IUBW). Model tests have also been performed to achieve an improved research performance using the designed hulls. Both numerical and experimental results show that the wave resistance of the hull forms can be effectively diminished if the bows are designed using the method introduced in this research. It is also expected that this research can facilitate better productivity in hull form design, especially at the preliminary design stage of a full ship type vessel.